Kelemahan Indonesia Menuju Poros Maritim Dunia dan Cara Mengatasinya - Suyanti; Zoelly's Fix Nurfadholi (Politeknik Ilmu Pelayaran Semarang, 2021)
This research examines Indonesia's weaknesses towards the world's maritime axis and how to overcome them. The problem under study is the Indonesian government's policy in realizing its aspirations to become a world maritime axis, weaknesses in realizing these ideals, and how to overcome them. This research is a descriptive study with a qualitative approach. The data used are secondary. Data collection is done by collecting books, journals, and references from various online media. The research found that the policies carried out by the government to realize the goal of becoming a world maritime axis, are: 1) Publishing a maritime legal conduct; 2) Describe the 5 pillars of the vision for the world's maritime axis; 3) Forming a Coordinating Ministry for Maritime Affairs; 4) Increase the export of marine commodities. Indonesia's weaknesses in realizing these ideals are overcome by the 5 pillars of the vision for the world's maritime axis, namely: 1) Decreasing maritime culture, overcome by the first pillar; 2) The absence of a common understanding of the concept of a maritime country, is overcome by the second pillar; 3) Lack of maritime human resources, overcome by the first pillar; 4) There are still overlapping regulations in the maritime sector, resolved by the fourth pillar; 5) The port management is still not well managed by the third pillar; 6) The lack of the role of sea transportation is overcome by the third pillar; 7) The small contribution of the marine fisheries sector is overcome by the second pillar; The existence of thuggery and port mafia is overcome by the fifth pillar.